Jurnal Quarter Life Crisis Pada Mahasiswa Pekerja Paruh Waktu FISIP Universitas Udayana - Perdania, Sellika; Punia, I Nengah; Aditya, I Gst. Ngr Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
The quarter-life crisis is not a new phenomenon in Indonesia, with many experiencing it without being familiar with the term. The quarter-life crisis is described as a state of instability, numerous choices, worries, and even despair experienced by individuals entering early adulthood (Robbins, 2001). This phase is typically encountered by individuals in their late teens to early twenties, including college students. The Faculty of Social and Political Sciences at Udayana University, located in the city center, is one of the faculties where students often work part-time jobs due to experiencing the quarter-life crisis. Using qualitative research methods, the author illustrates how this phase influences social and psychological aspects (both positively and negatively), leading students at Udayana's Faculty of Social and Political Sciences to choose part-time work as one of their alternatives. Through the Theory of Emerging Adulthood, one characteristic of this period is being self-focused, where young adults focus on themselves to make life choices, reducing their dependence on parents or others.